2018
DOI: 10.1037/adb0000349
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol intoxication on young adult women’s identification of risk for sexual assault: A systematic review.

Abstract: Alcohol-related sexual assault among young adult women continues to present a public health concern. Social information-processing theory provides an organizing framework for understanding how alcohol intoxication can impair the processing of sexual assault risk cues and behavioral responding in sexual assault scenarios. The aim of the present article was to systematically review the extant research on the effects of alcohol intoxication on sexual assault risk information processing among young adult women. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…The intoxicated bystander then focuses on his or her own experiences rather than attending to the experience of others, reducing the likelihood of an intervention response. Alcohol may also interfere with information processing related to sexual risk among potential victims (Melkonian & Ham, 2018) and potential perpetrators (Abbey et al, 2014) as well as with a bystander's ability to notice and accurately interpret risk for sexual assault. In examining bystander intervention for alcoholinvolved sexual assaults using qualitative interviews, Pugh and colleagues (2016) found that failing to identify that the victim was in danger was the primary barrier to intervention.…”
mentioning
confidence: 99%
“…The intoxicated bystander then focuses on his or her own experiences rather than attending to the experience of others, reducing the likelihood of an intervention response. Alcohol may also interfere with information processing related to sexual risk among potential victims (Melkonian & Ham, 2018) and potential perpetrators (Abbey et al, 2014) as well as with a bystander's ability to notice and accurately interpret risk for sexual assault. In examining bystander intervention for alcoholinvolved sexual assaults using qualitative interviews, Pugh and colleagues (2016) found that failing to identify that the victim was in danger was the primary barrier to intervention.…”
mentioning
confidence: 99%
“…Hookups involve isolation, sexual expectations, and the potential for misunderstanding and miscommunication of sexual intent, all factors that can contribute to the risk of sexual victimization. The presence of alcohol at the time of sexual activity exacerbates difficulties in perception, communication, and responses (Melkonian & Ham, 2018), while increasing male sexual aggression within sexual encounters (Testa, Brown, & Wang, 2018). Alcoholinvolved hookups are also likely to be less well-planned (Livingston, Testa, Windle, & Bay-Cheng, 2015) and more likely to involve partners who are less well-known (LaBrie et al, 2014;Testa & Collins, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…First, women who drink to the point of incapacitation or unconsciousness are vulnerable to incapacitated rape, i.e., unwanted intercourse that occurs because the victim is unable to consent, respond, or object . Intoxication at less extreme levels may contribute to sexual victimization indirectly as a result of alcohol-related impairment in the ability to recognize, interpret, and respond to sexual assault risk cues (Melkonian & Ham, 2018).…”
Section: Heavy Episodic Drinking and Vulnerability To Sexual Victimizmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact, in and of itself, has significant complications because it is relatively common for women assaulted by an acquaintance to not report sexual assaults because they do not expect to be believed (e.g., Bachman, 1998;Koss, Dinero, Seibel, & Cox, 1988). A second difference for campus sexual assaults from criminal cases, is that campus cases more likely involve substance use by both the perpetrator and the victim (Abbey, 2002;Melkonian & Ham, 2018). If a victim were known to be drinking, doubts fueled by rape myths may alter the picture of a blameless victim, thus potentially leading to attributions of responsibility based on the victim's substance use rather than on the perpetrator's behavior (Hayes, Abbott, & Cook, 2016).…”
Section: Assessment Of Victims As Matching Stereotypes Of "Real Rapes"mentioning
confidence: 99%